Synergistic Impact of Systolic Blood Pressure and Perfusion Status on Mortality in Acute Heart Failure. (8th March 2021) - Rossello, Xavier; Bueno, Héctor; Gil, Víctor; Jacob, Javier; Martín-Sánchez, Francisco Javier; Llorens, Pere; Herrero Puente, Pablo; Alquézar-Arbé, Aitor; Espinosa, Begoña; Raposeiras-Roubín, Sergio; Müller, Christian E.; Mebazaa, Alexandre; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Physical examination remains the cornerstone in the assessment of acute heart failure. There is a lack of adequately powered studies assessing the combined impact of both systolic blood pressure (SBP) and hypoperfusion on short-term mortality. Methods: Patients with acute heart failure from 41 Spanish emergency departments were recruited consecutively in 3 time periods between 2011 and 2016. Logistic regression models were used to assess the association of 30-day mortality with SBP (<90, 90–109, 110–129, and ≥130 mm Hg) and with manifestations of hypoperfusion (cold skin, cutaneous pallor, delayed capillary refill, livedo reticularis, and mental confusion) at admission. Results: Among 10 979 patients, 1143 died within the first 30 days (10.2%). There was an inverse association between 30-day mortality and initial SBP (35.4%, 18.9%, 12.4%, and 7.5% for SBP<90, SBP 90–109, SBP 110–129, and SBP≥130 mm Hg, respectively; P <0.001) and a positive association with hypoperfusion (8.0%, 14.8%, and 27.6% for those with none, 1, ≥2 signs/symptoms of hypoperfusion, respectively; P <0.001). After adjustment for 11 risk factors, the prognostic impact of hypoperfusion on 30-day mortality varied across SBP categories: SBP≥130 mm Hg (odds ratio [OR]=1.03 [95% CI, 0.77–1.36] and OR=1.18 [95% CI, 0.86–1.62] for 1 and ≥2 compared with 0 manifestations of hypoperfusion), SBP 110 to 129 mm Hg (OR=1.23 [95% CI, 0.86–1.77] and OR=2.18 [95% CI, 1.44–3.31], respectively), SBP 90 to 109 mm Hg (OR=1.29 [95% CI, 0.79–2.10] and OR=2.24 [95% CI, 1.36–3.66], respectively), and SBP<90 mm Hg (OR=1.34 [95% CI, 0.45–4.01] and OR=3.22 [95% CI, 1.30–7.97], respectively); P -for-interaction =0.043. Conclusions: Hypoperfusion confers an incremental risk of 30-day all-cause mortality not only in patients with low SBP but also in normotensive patients. On admission, physical examination plays a major role in determining prognosis in patients with acute heart failure.